Association of Hypothyroidism With Type 2 Diabetes Mellitus: A Hospital Based Experience in a Tertiary Care Centre - Faruque, Farhana; Islam, Naylla; Ul bashar, SM Sufi Shafi; Chatterjee, Mohua; Uddin, Zahir (Bangladesh Journal of Medicine, 2022)
Background:Thyroid diseases and diabetes mellitus are the two most common endocrine disorders encountered in clinical practice. Type 2 diabetes mellitus (T2DM) has an intersecting underlying pathology with thyroid dysfunction. Insulin and thyroid hormones are intimately involved in cellular metabolism and thus excess or deficit of either of these hormones result in the functional derangement of the other.Despite the absence of definite guidelines regarding screening for thyroid dysfunction in diabetic patients, in the view of this incidence together with the mutual effect of the common two endocrinopathies on each other and the increased risk of complications in diabetic patients in the setting of abnormal thyroid dysfunction, a systematic approach to thyroid testing in diabetic patients is favorable. Methods:A Cross sectional descriptive observational study was performed at a tertiary care centre.Patients of 30 years and older with known type 2 DM without thyroid disorders between March 2018 to September 2018 were included in this study by purposive sampling technique.A total of 100 patients were included in the study. Results:Among the study patients, 13(26%) had thyroid abnormalities, 8 cases were male and 5 cases were female. Thyroid abnormality was associated with duration of DM. The mean duration of disease was 6.28±2.57 years in patients with normal thyroid profile group and 10.92±8.13 years in patients with abnormal thyroid profile (hypothyroidism or hyperthyroidism) group. Patients with poor glycemic control prone to develop endocrinopathies like thyroid abnormality. HbA1c also shows the positive correlation with thyroid abnormality in type 2 diabetes patients. Regarding the definition of thyroid abnormality, 7% patients had Primary hypothyroidism, 2% Subclinical hypothyroidism and 3% primary hyperthyroidism and single case subclinical hyperthyroidism. Conclusion: Our results demonstrate that hypothyroidism is the common thyroid disorder in type 2 DM patient. It seems that unidentified thyroid dysfunction could positively impact diabetes and its complications. The ability to diagnose and treat unsuspected thyroid dysfunction in these patients may greatly enhance the quality of life. Hence the need to detect such cases where thyroid dysfunction contributes to morbidity and where it is the cause for poor control of the associated conditions. Bangladesh J Medicine 2022; 33: 193-201